Analyzing the impact of digital technology on consumers’ travel intentions - Yanan Tan; Guoliang Jiang; Shaheem Sayed Merajuddin; Fang Zhao (Journal of Innovation & Knowledge)
With the objective of providing insights and strategic recommendations to enhance the competitiveness of tourism destinations, this study endeavors to examine the nuanced impact of digital technology utilization on the travel intentions of consumers. A comprehensive theoretical framework is developed, incorporating five key mechanisms to elucidate how digital device usage influences consumers’ propensity to travel. Empirical findings indicate that the expansion of information channels and the broadening of social networks constitute the most significant mechanisms through which smartphone usage affects travel intentions. These effects are followed by the enhancement of mutual trust and life convenience, while the augmentation of income levels exerts the weakest influence. Furthermore, this study extends its analysis to the heterogeneous effects of smartphone and digital device adoption across different consumer demographics. The data suggest that the influence of digital technology on travel intentions is particularly pronounced among the middle-aged and elderly, males, extroverts, those with a more pessimistic worldview, and lower-income groups. Drawing upon these findings, this study proposes targeted policy and managerial implications aimed at optimizing the impact of digital technology on travel intentions. These recommendations emphasize innovations in tourism marketing communication channels, the enhancement of tourism service offerings, and the advancement of digital infrastructure, with a focus on aligning digital adoption strategies with the distinctive characteristics of diverse consumer segments.